Dielectric Spectroscopy: Yesterday, Today and Tomorrow - Friedrich Kremer; Martin Tress (Applied Sciences, 2025)
The theory of orientational polarization and dielectric relaxation was developed by P. Debye more than 100 years ago. It approximates a molecule by a sphere having one or more dipole moments. While in the beginning the experimentally accessible spectral range was limited to roughly 6 decades in frequency, at the end of the last century, novel spectroscopic techniques were developed and dielectric spectroscopy became broadband, nowadays covering 18 decades with no gaps.This paved the avenue for a multitude of novel fields of research in soft matter and solid-state physics including fundamental questions like the scaling of relaxation processes or the dynamics of glasses. Yet the analysis of dielectric spectra is still based on the classical approach by Debye which does not consider the multitude of intra- and inter-molecular interactions within a molecular system. To experimentally overcome these principal limitations, it is suggested to take advantage of the molecular specificity of the infrared spectral range. This offers the unique possibility to realize a novel “Orientational Polarization Spectroscopy”, in which the orientational response of a molecular system can be analyzed on an atomistic scale. For that, the theory will be outlined and the first experimental results will be presented.